Two-stage instrumental variables identification of polynomial Wiener systems with invertible nonlinearities - Janczak, Andrzej; Korbicz, Józef (1951- ) (Zielona Góra: Uniwersytet Zielonogórski)
A new two-stage approach to the identification of polynomial Wiener systems is proposed. It is assumed that the linear dynamic system is described by a transfer function model, the memoryless nonlinear element is invertible and the inverse nonlinear function is a polynomial. Based on these assumptions and by introducing a new extended parametrization, the Wiener model is transformed into a linear-in-parameters form. In Stage I, parameters of the transformed Wiener model are estimated using the least squares (LS) and instrumental variables (IV) methods.
Keywords: nonlinear systems; parameter estimation; dynamic models; polynomial models